Harnessing the probiotic properties and immunomodulatory effects of fermented food-derived Limosilactobacillus fermentum strains: implications for environmental enteropathy - Prakash, Vidhya; Madhavan, Aravind; Veedu, Archana Palillam; Babu, Pradeesh; Jothish, Abhirami; Nair, Sruthy S.; Suhail, Alin; Prabhakar, Meera; Sain, Thasleema; Rajan, Raveena; Somanathan, Priyanka; Abhinand, Kuniyil; et al. (Frontiers in Nutrition, 2023)
Introduction: Environmental enteropathy (EE), a chronic small intestine disease characterized by gut inflammation, is widely prevalent in low-income countries and is hypothesized to be caused by continuous exposure to fecal contamination. Targeted nutritional interventions using potential probiotic strains from fermented foods can be an effective strategy to inhibit enteric pathogens and prevent chronic gut inflammation. Methods: We isolated potential strains from fermented rice water and lemon pickle and investigated their cell surface properties, antagonistic properties, adhesion to HT-29 cells, and inhibition of pathogen adherence to HT-29 cells. Bacteriocin-like inhibitory substances (BLIS) were purified, and in vivo survival studies in C. elegans infected with Salmonella enterica was performed. We further checked the expression pattern of pro and anti-inflammatory cytokines (IL-6, IL8, and IL-10) in HT29 cells supplemented with strains. Results: The strains isolated from rice water (RS) and lemon pickle (T1) were identified as Limosilactobacillus fermentum MN410703 and MN410702, respectively. Strains showed probiotic properties like (tolerance to low pH (pH 3.0), bile salts up to 0.5%, simulated gastric juice at low pH, and binding to extracellular matrix molecules. Auto-aggregation of T1 was in the range of 85% and significantly co-aggregated with Klebsiella pneumoniae, Salmonella enterica, and Escherichia coli at 48%, 79%, and 65%, respectively. Both strains had a higher binding affinity to gelatin and heparin compared to Bacillus clausii. Susceptibility to most aminoglycoside, cephalosporin, and macrolide classes of antibiotics was also observed. RS showed BLIS activity against K. pneumoniae, S. aureus, and S. enterica at 60%, 48%, and 30%, respectively, and the protective effects of BLIS from RS in the C. elegans infection model demonstrated a 70% survival rate of the worms infected with S. enterica. RS and T1 demonstrated binding efficiency to HT29 cell lines in the range of 38-46%, and both strains inhibited the adhesion of E. coli MDR and Salmonella enterica. Upregulation of IL-6 and IL-10 and the downregulation of IL-8 were observed when HT29 cells were treated with RS, indicating the immunomodulatory effects of the strain. Discussion: The potential strains identified could be an effective strategy to inhibit enteric pathogens and prevent environmental enteropathy.